Rancang Bangun Marketplace Jasa Desain Dengan Menggunakan Metode Content-Based Filtering - Suwarno Suwarno; Tedy Fernando (Prosiding, 2022)
The public's need for design services is getting higher, it opens up opportunities for freelancers to offer the design services. Marketplace is a solution to connect the service between users and freelancers. Therefore, the design of the service marketplace needs to be designed smart enough to be able to provide appropriate recommendations and accordance with the user needs. This study builds a web-based design service marketplace that implements a recommendation system with a content-based filtering method with a cosine similarity algorithm that is applied to two objects, namely tags defined by freelancers and users. The results of the study indicate that the design service marketplace system has provided recommendation results in the form of a list of freelancers according to user tags.